2017
DOI: 10.1111/ggi.13214
|View full text |Cite
|
Sign up to set email alerts
|

Once frail, always frail? Frailty transitions in home care users with intellectual and developmental disabilities

Abstract: While many experience worsening of frailty status, stability and improvement are viable goals of care. Future research should examine the rate at which non-frail, pre-frail and frail individuals accumulate deficits, as well as the impact of home care services on frailty. Geriatr Gerontol Int 2018; 18: 547-553.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(44 citation statements)
references
References 24 publications
5
39
0
Order By: Relevance
“…The present study showed that frailty status can deteriorate to a worse state (22.2%) but can also turn back to a better state (7.8%), though the majority stayed in the same state (70.0%). These results are similar to previous studies, [33,38,39] and continue to support the notion that frailty is a dynamic and reversible status in later life. [40] With increasing age, the risk of being frailty and frailty worsening were both higher.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study showed that frailty status can deteriorate to a worse state (22.2%) but can also turn back to a better state (7.8%), though the majority stayed in the same state (70.0%). These results are similar to previous studies, [33,38,39] and continue to support the notion that frailty is a dynamic and reversible status in later life. [40] With increasing age, the risk of being frailty and frailty worsening were both higher.…”
Section: Discussionsupporting
confidence: 93%
“…However, after adjusting for lifestyle factors, it seemed that few differences in changes of frailty were consistent with previous studies. [18,39] These findings suggest that females probably have worse health but a more protective lifestyle, which provides a reason for the health-survival paradox. A higher educational level, known to promote better psychological well-being and less dependence, [42] was found to be associated with decreasing frailty among baseline robust elders in a previous study [22] and in the current study.…”
Section: Discussionmentioning
confidence: 95%
“…The present study showed that frailty status can deteriorate to a worse state (22.2%) but can also turn back to a better state (7.8%), though the majority stayed in the same state (70.0%). These results are similar to previous studies, [33,38,39] and continue to support the notion that frailty is a dynamic and reversible status in later life [40]. With increasing age, the risk of being frailty and frailty worsening were both higher.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the decline rate among robust and prefrail female elders was found to be higher than in males. However, after adjusting for lifestyle factors, it seemed that few differences in changes of frailty were consistent with previous studies [18,39]. These findings suggest that females probably have worse health but a more protective lifestyle, which provides a reason for the health-survival paradox.…”
Section: Discussionsupporting
confidence: 88%
“…Once identified as pre-frail or frail, it is important to recognize that there exists both a risk of future decline and an opportunity for improvement. 24,25 Sudden, rapid decline although more often seen among those who are frail, is also a risk for those who are pre-frail.…”
Section: Improvement and Maintenance Are Viable Goalsmentioning
confidence: 99%